Efeitos da prematuridade sobre o desenvolvimento de lactentes - Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Bolsoni-Silva, Alessandra Turini [UNESP] (My University, 2011)
The aim of this study was to evaluate the behavioral aspects of infants relating them to prematurity. A total of 130 lactentes were evaluated every month during the first year of life, employing the Operational Portage Inventory . Group 1, 56 newborns with no life risk at birth and Group 2, 74 premature babies, those that was born until 37 gestation weeks. The outcomes obtained showed that the premature babies (Group 2) presented a totally different performance than Group 1 in 68% of the analyses made, especially for motor development, cognition and socialization. The outcomes are in accord to the ones obtained in the literature, which indicate prematurity as one of the most harmful proximal conditions for the development of infants.

Foi avaliado o desenvolvimento de lactentes, correlacionando-o com a prematuridade. Participaram do estudo 130 lactentes que foram avaliados mensalmente no decorrer do primeiro ano de vida com o Inventário Portage Operacionalizado. Desses, 56 eram sem condição de risco identificados por ocasião do nascimento (Grupo 1) e 74 eram nascidos prematuros (Grupo 2), até 37 semanas de gestação. Os resultados obtidos apontaram que os lactentes do Grupo 2 apresentaram desempenhos significantemente inferior aos do Grupo 1 em 68% das análises conduzidas, com destaque para as áreas de desenvolvimento motor, cognição e socialização. Tais resultados são condizentes com os obtidos na literatura que apontam a prematuridade como uma das condições proximais mais prejudiciais ao desenvolvimento de lactentes.
Effects of the prematurity on the development of lactentes
Keywords: Operational portage inventory; Development of lactentes; Infantile evaluation; Prematurity; Inventário Portage operacionalizado; Desenvolvimento de lactentes; Avaliação infantil; Prematuridade